2009
DOI: 10.1007/s00270-009-9770-9
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Local Progression After Computed Tomography-Guided Percutaneous Radiofrequency Ablation for Unresectable Lung Tumors: 9-Year Experience in a Single Institution

Abstract: The purpose of this study was to retrospectively determine the local control rate and contributing factors to local progression after computed tomography (CT)-guided radiofrequency ablation (RFA) for unresectable lung tumor. This study included 138 lung tumors in 72 patients (56 men and 16 women; age 70.0 +/- 11.6 years (range 31-94); mean tumor size 2.1 +/- 1.2 cm [range 0.2-9]) who underwent lung RFA between June 2000 and May 2009. Mean follow-up periods for patients and tumors were 14 and 12 months, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 23 publications
1
23
1
1
Order By: Relevance
“…Alternatively, this difference in size threshold could be due to the higher incidence of metastatic tumors in the study by Yashiro et al or differences in cryoprobe sizes, although both the study by Yashiro et al (4) and the present study used the Endocare system. Previous work on RF ablation also established larger tumor size as a risk factor for local progression, although some studies report a 2-cm threshold (17,18), and another reported a 3-cm threshold (19). In contrast to the study by Yashiro et al (4), this study did not find that proximity to a large vessel (diameter 4 3 mm) was predictive of local progression.…”
Section: Discussioncontrasting
confidence: 76%
“…Alternatively, this difference in size threshold could be due to the higher incidence of metastatic tumors in the study by Yashiro et al or differences in cryoprobe sizes, although both the study by Yashiro et al (4) and the present study used the Endocare system. Previous work on RF ablation also established larger tumor size as a risk factor for local progression, although some studies report a 2-cm threshold (17,18), and another reported a 3-cm threshold (19). In contrast to the study by Yashiro et al (4), this study did not find that proximity to a large vessel (diameter 4 3 mm) was predictive of local progression.…”
Section: Discussioncontrasting
confidence: 76%
“…Pneumothorax during or subsequent to RFA in this series was also in line with the reported rates in the literature [14,21] and had no impact on local recurrences as well. Furthermore, as a major complication, we observed a single hemothorax with the bleeding originating from the RF-probe insertion into the middle lobe.…”
Section: Discussionsupporting
confidence: 80%
“…60 Signs of relapse can be very subtle, particularly on early followup CT. Any change in lesion contour, increase in volume or contrast enhancement after 6 months is highly suspicious (Figures 8 and 9); however, there are no well-defined criteria to assess post-ablation appearances on CT. A recent study has described the following features as being most useful: a change in dynamic enhancement (increasing contrast material uptake in the ablation zone, nodular enhancement measuring .10 mm, any central enhancement .15 HU and enhancement greater than baseline at any time after ablation) and growth of the treatment zone after 3 months, peripheral nodular growth and change from GGO to solid opacity. 61 Modalities other than CT have been used to follow up ablated tumours.…”
Section: Tumour Recurrencementioning
confidence: 99%